Group II and III mGluRs-mediated presynaptic inhibition of EPSCs recorded from hippocampal interneurons of CA1 stratum lacunosum moleculare. - Price, C; Karayannis, T; Pál, B; Capogna, M (2005)
We have studied the effects of groups II and III metabotropic glutamate receptor (mGluR) activation on excitatory responses recorded from hippocampal interneurons of CA1 stratum lacunosum moleculare (SLM). Excitatory postsynaptic currents (EPSCs) evoked by stimulation of the perforant pathway were reduced either by the group II mGluR agonist LY354740 (50-100 nM, 49.1+/-5.7% of control) or by the group III mGluR agonist l-2-amino-4-phosphonobutyric acid (l-AP4) (50 microM, 36.8+/-4.4% of control). Both drugs significantly enhanced paired-pulse facilitation of the EPSCs. Furthermore, both 100 nM LY354740 and 50 microM l-AP4 reduced the frequency, but not the amplitude, of miniature excitatory synaptic currents (mEPSCs), recorded in the presence of 1 microM TTX and 50 microM picrotoxin, or EPSCs evoked by perforant pathway stimulation in the presence of 2.5 mM Sr2+. The broad-spectrum mGluR antagonist LY341495 (10-50 microM) did not affect test EPSCs elicited 210 ms after stimulation at 100 Hz. At network level, 1-5 microM LY354740 significantly reduced the power of gamma frequency oscillations induced by 20 microM carbachol, 600 nM kainate and 5 mM K+ in hippocampal CA1 area. Our results show powerful modulation of excitatory transmission impinging on interneurons of CA1 SLM by presynaptic group II or III mGluRs.